Fouling mitigation in forward osmosis and membrane distillation for desalination - Nidal Hilal (Desalination, 2020)
Freshwater scarcity is one of the grand challenges that has posed threats to the global economy, societal stability and ecosystem balance. Desalination has been long recognized as an effective approach for fresh water production from seawater and brackish water. Forward osmosis (FO) is currently one of the most studied technologies for seawater and brackish water desalination due to its intrinsic advantages compared to reverse osmosis. On the other hand, membrane distillation (MD) is an emerging technology to offer a potentially cost effective thermally-driven desalination process, especially when coupled with waste heat and solar thermal. One major and inevitable challenge for FO and MD is membrane fouling. For decades, fouling and its related topics have gained extensive attention from the desalination communities and various strategies have been implemented to tackle this long standing issue. In this contribution, the fouling mitigation strategies in terms of pretreatment, membrane surface modification and operating conditions for both FO and MD processes are comprehensively reviewed.